How do Laboratory Friction Parameters Compare With Observed Fault Slip and Geodetically Derived Friction Parameters? Insights From the Longitudinal Valley Fault, Taiwan. Issue 10 (1st October 2021) - den Hartog, S. A. M.; Thomas, M. Y.; Faulkner, D. R.
Abstract: Laboratory measurements of constitutive frictional parameters are commonly inferred to explain the wide variety of slip behavior seen on natural faults. The extent to which these small‐scale measurements directly relate to fault slip behavior remains obscure. In this work, we compare laboratory‐determined frictional parameters on surface‐derived samples from along the length of the Longitudinal Valley Fault (LVF) in Taiwan with the observed slip behavior and with frictional parameters obtained geodetically. The LVF displays partially locked and creeping sections and a M w 6.8 event in 2003 produced transient acceleration of slip in the adjacent creeping sections that can be used to determine the frictional parameters for direct comparison with the laboratory‐measured ones. We find that the laboratory‐measured friction parameters are markedly different for samples collected from the creeping and partially locked sections of the fault, the former showing lower friction coefficients and more positive values of the fault stability parameter ( a−b ). Moreover, values for the product of ( a−b ) and the effective normal stress, determined geodetically, relate very closely to those measured in the laboratory. Mineralogical and microstructural analyses of the fault gouges show that some mineralogically similar gouges produce distinctly different frictional behavior, and that this may be related to the presence and distribution of kaolinite. We conclude overall that upscaling of laboratory measurements of fault frictional properties appears to reflect well the large‐scale slip behavior of faults. Plain Language Summary: Tectonic faults contained within the Earth's crust can sometimes slip in continuous slow steady motion, known as "creep." They can also sometimes slip in a more episodic fashion, during earthquakes, and stay locked the rest of the time. Both behaviors result in different surface movement, quantifiable via geodetic methods. Models of fault slip behavior typically rely on data derived from laboratory friction measurements on rocks from fault zones. However, it is unclear whether the small‐scale laboratory measurements directly relate to observed large‐scale fault behavior. Here, we used fault rock samples from the Longitudinal Valley Fault (LVF) in Taiwan to compare the results from laboratory measurements with the slip behavior and inferred frictional properties from geodetic observations. Samples were taken both from the partially locked and creeping parts of the fault. We performed laboratory measurements on these samples that yield results that correctly predict either earthquake slip or creep. We also used the geodetic measurements of the LVF to derive the same parameters that are measured in the laboratory and find they compare well. We conclude that small‐scale laboratory measurements indeed reflect the intrinsic frictional properties of the LVF that result in the observed large‐scale behavior of this major tectonic fault. Key Points: Laboratory‐determined frictional parameters are compared with those obtained geodetically and with observed fault slip behavior Derived friction parameters correspond well with each other and are distinctive for creeping and partially locked sections of the fault Upscaling of laboratory measurements of fault frictional properties reflects the large‐scale slip behavior of faults well